2012
DOI: 10.1182/blood-2012-04-423079
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2 trial of standard-dose cyclophosphamide, doxorubicin, vincristine, prednisone (CHOP) and rituximab plus bevacizumab for patients with newly diagnosed diffuse large B-cell non-Hodgkin lymphoma: SWOG 0515

Abstract: S0515 was a phase 2 trial to determine whether the addition of bevacizumab to cyclophosphamide, doxorubicin, vincristine, prednisone (CHOP) plus rituximab (R-CHOP) would improve progressionfree survival (PFS) without adding significant toxicity in patients with newly diagnosed advanced diffuse large B-cell lymphoma. A total of 73 patients were enrolled. For the 64 eligible patients, median age was 68 years, and 60% had International Prognostic Index scores more than or equal to 3. The observed 1-and 2-year PFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 45 publications
(56 reference statements)
1
47
0
Order By: Relevance
“…The use of bevacizumab in lymphoma patients is still under debate due to the limited efficacy and associated toxicities (47) and should be restricted to lymphoma types with proven efficacy (48). In this context, our data indicate that patients with ALK-rearranged ALCL may indeed benefit with treatment with bevacizumab.…”
Section: Discussionmentioning
confidence: 70%
“…The use of bevacizumab in lymphoma patients is still under debate due to the limited efficacy and associated toxicities (47) and should be restricted to lymphoma types with proven efficacy (48). In this context, our data indicate that patients with ALK-rearranged ALCL may indeed benefit with treatment with bevacizumab.…”
Section: Discussionmentioning
confidence: 70%
“…However, we found the addition of bevacizumab to R-CHOP exacerbated the cardiac risk seen with doxorubicin alone, a risk that was also observed in a phase II trial that was published after the current study had been designed and carried out. 26 In both the RA-CHOP and R-CHOP arms, the incidence of CHF events increased beginning at a cumulative doxorubicin dose of 200 mg/m 2 . However, while the event rate plateaued in the R-CHOP group despite increasing cumulative doxorubicin doses up to 400 mg/m 2 , it continued to increase in the RA-CHOP arm, particularly beyond a cumulative dose of doxorubicin of 300 mg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…26 Data from the SWOG 0515 trial did not become available until after the discontinuation of bevacizumab treatment in the MAIN study.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, clinical trials using an anti-vascular endothelial growth factor (VEGF) antibody (bevacizumab) in an attempt to inhibit lymphoma angiogenesis in patients with DLBCL or mantle cell lymphoma failed to show meaningful antitumor efficacy. 4,5 pericyte function. Importantly, this approach resulted in significant inhibition of human lymphoma growth in vivo.…”
mentioning
confidence: 99%
“…It has been suggested that one reason anti-VEGF therapy has not succeeded in the treatment of patients with lymphoma is that other proangiogenic mechanisms were not disabled via this approach. 4 Targeting the PDGFRb 1 pericyte, which regulates multiple pathways involved in the maintenance and proliferation of vascular ECs, represents an attractive strategy to dismantle the lymphoma vasculature and, perhaps, the lymphoma itself.…”
mentioning
confidence: 99%